The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/tbj.12546
|View full text |Cite
|
Sign up to set email alerts
|

Do Primary Care Physician Perform Clinical Breast Exams Prior to Ordering a Mammogram?

Abstract: Both the American Cancer Society and National Comprehensive Cancer Network recommend annual clinical breast examination (CBE) along with screening mammogram (SM) for patients starting at 40 years of age. However, patients with a palpable breast mass should have a diagnostic mammogram (DM) during workup. Review at our institution demonstrated that 11% of patients with newly diagnosed breast cancer and self-identified breast mass had SM instead of DM. This led us to question whether primary care physicians (PCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In Brazil, strategies for early breast cancer diagnosis must take a three‐pronged approach comprising a population aware of the signs and suspicious symptoms of the disease, health professionals qualified to evaluate even difficult‐to‐detect cancer cases and qualified health services, in order to guarantee integral medical assistance (Brasil, ). It is possible to assess facilitators regarding this process, during gynaecological consultations, as health professionals may promote education and awareness actions directed to interventions, such as clinical breast exams and mammograms (Larson, Cowher, O'Rourke, Patel, & Pratt, ). Because of this, it is supposed that women who frequently attend gynaecological consultations are more likely to detect breast cancer in its early stages (Azenha et al, ; Larson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, strategies for early breast cancer diagnosis must take a three‐pronged approach comprising a population aware of the signs and suspicious symptoms of the disease, health professionals qualified to evaluate even difficult‐to‐detect cancer cases and qualified health services, in order to guarantee integral medical assistance (Brasil, ). It is possible to assess facilitators regarding this process, during gynaecological consultations, as health professionals may promote education and awareness actions directed to interventions, such as clinical breast exams and mammograms (Larson, Cowher, O'Rourke, Patel, & Pratt, ). Because of this, it is supposed that women who frequently attend gynaecological consultations are more likely to detect breast cancer in its early stages (Azenha et al, ; Larson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to assess facilitators regarding this process, during gynaecological consultations, as health professionals may promote education and awareness actions directed to interventions, such as clinical breast exams and mammograms (Larson, Cowher, O'Rourke, Patel, & Pratt, 2016). Because of this, it is supposed that women who frequently attend gynaecological consultations are more likely to detect breast cancer in its early stages (Azenha et al, 2011;Larson et al, 2016). American researchers TA B L E 3 Factors to the delay in symptomatic presentation on women's perception (data from 182 women who thought that there was a delay) concluded that women who do not frequently use health services and seek out less preventive attention are more prone to delays in presentation (Rauscher et al, 2010).…”
Section: The Observed Time Interval Was Shorter In Countries Such Asmentioning
confidence: 99%
“…8,36 This suggested that our sample was not following older screening recommendations across cancer sites/breast cancer screening behaviors but receiving clinical breast exams and possibly mammography referrals during annual visits with their primary care providers. 47,48 However, it is not clear whether Black women are receiving guidance that reflects pre-USPSTF recommendations or no screening recommendation at all during these encounters. Research has documented that providers are less likely to recommend mammography screening to Black women compared to their White patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective measures to reduce breast cancer mortality is early detection (Amasha 2013;Larson et al 2016;O'Mahony et al 2017;Somayyeh and Aydogdu 2019). Breast cancer research, early detection and treatment have increased the survival rate of cancer patients, but not the incidence of breast cancer.…”
Section: Introductionmentioning
confidence: 99%